Diastereoselective sulfonate-directed carbonyl reduction of γ-keto-sulfonates. Issue 19 (9th May 2019) - McLaughlin, Noel; Duffy, Colm; Alletto, Francesco; Ravelli, Andrea; Lancianesi, Stefano; Gillick-Healy, Malachi; Adamo, Mauro F.A.
Graphical abstract: Highlights: A new hitherto unreported directing group for diastereoselective synthesis is reported. A method for the preparation of hydroxyl sulfonates in high yield and diastereoselectivity is provided. Data for a family of 12 ketosulfonates and 12 γ-hydroxysulfonates is reported. Abstract: The diastereoselective reduction of γ-keto-sulfonates to afford α, γ-substituted γ-hydroxy sulfonates has been investigated. Herein we report the first example of a diastereoselective carbonyl reduction whereby hydride attack is directed via chelation of a neighbouring sulfonate group to a boron atom, thus affording prevalently trans γ-hydroxy sulfonates.